Storytelling sebagai Alat Pedagogis dalam Pengajaran Bahasa Arab: Meningkatkan Keterampilan Berbicara - Solehudin, Muhamad (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study explores the effectiveness of storytelling as a pedagogical strategy for enhancing speaking proficiency (MahÄrah KalÄm) in Arabic language education. Recognizing the limitations of conventional, grammar-focused instruction, this research proposes storytelling as an alternative approach that fosters spontaneous language use, strengthens vocabulary retention, and improves learnersâ€™ syntactic awareness. Using a qualitative case study design, the research was conducted at Pondok Pesantren Darullughah Waddaâ€™wah, involving 40 senior high school students aged 17â€“18. Data were collected through classroom observations, student reflections, and teacher interviews during a six-week instructional program integrating storytelling into Arabic speaking classes. The findings reveal that storytelling not only increases student motivation and confidence but also reinforces core language structures in a meaningful context. Storytelling activities provided an emotionally safe environment that promoted oral participation and collaborative interaction. This study highlights the pedagogical potential of traditional storytelling in Arabic instruction and encourages its integration into communicative language teaching frameworks for more effective speaking outcomes.